Liquid pedagogy: Pedagogical imaginary or Educational Theory? - Xavier LAUDO CASTILLO (Ediciones Universidad de Salamanca, 2015)
This paper introduces a specific problem within the broader research on liquid pedagogy. The article displays the meaning of the liquid metaphor applied to pedagogy and two possible uses of the signifier «liquid pedagogy»: a) as a pedagogical imaginary, and b) as a theory of education. I discuss the liquid pedagogy as a theory that can be useful for articulating the idea of what education is and what should be. Two possible variants of the liquid pedagogy are described: a) with solid methods to convey tradition b) with liquid methods to yield new possibilities. Taking into account that the pedagogical imaginary is the general framework of any theory of education -liquid or solid-, I claim, on the one hand, the use of the term «postmodern pedagogical imaginary». On the other hand, I propose the use of the term «liquid pedagogy» as a theory of education in which the key element is the unexpected character of the educational results.